2022
DOI: 10.5194/aab-65-207-2022
|View full text |Cite
|
Sign up to set email alerts
|

Status quo of genetic improvement in local goats: a review

Abstract: Abstract. This review aims to summarize and synthesize the fragmented information available on the genetic improvement of local goats (criollo, indigenous, native) on the American and other continents, where populations with these goats have an important role in food security and the economy of rural communities, as well as in conservation of biodiversity and productivity improvement. Topics such as the current state of goat production globally, conservation programs, resistance to parasites and diseases, use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…: 22.6% of all herds; Skopelos: 2.5%; and indigenous Capra prisca: 25.6%) [24]. In general, indigenous breeds of sheep and goats are considered to be less susceptible to disease threats than many mainstream, high-production breeds [25,26], and relevant findings have also been reported regarding Greek breeds [27,28]. Moreover, indigenous breeds of sheep and goats are considered to be more tolerant to adverse weather conditions; previous studies have reported genetic differences in adaptation to temperature stress and, thus, resilience to extreme temperatures [29,30], which are mediated through a complex network of genes [31,32].…”
Section: Relevance Of Findingsmentioning
confidence: 99%
“…: 22.6% of all herds; Skopelos: 2.5%; and indigenous Capra prisca: 25.6%) [24]. In general, indigenous breeds of sheep and goats are considered to be less susceptible to disease threats than many mainstream, high-production breeds [25,26], and relevant findings have also been reported regarding Greek breeds [27,28]. Moreover, indigenous breeds of sheep and goats are considered to be more tolerant to adverse weather conditions; previous studies have reported genetic differences in adaptation to temperature stress and, thus, resilience to extreme temperatures [29,30], which are mediated through a complex network of genes [31,32].…”
Section: Relevance Of Findingsmentioning
confidence: 99%